Genomic Epidemiology and Molecular Resistance Mechanisms of Azithromycin-Resistant Neisseria gonorrhoeae in Canada from 1997 to 2014 - Demczuk, Walter (J Clin Microbiol, 2016)
The emergence of Neisseria gonorrhoeae strains with decreased susceptibility to cephalosporins and azithromycin (AZM) resistance (AZM(r)) represents a public health threat of untreatable gonorrhea infections. Genomic epidemiology through whole-genome sequencing was used to describe the emergence, dissemination, and spread of AZM(r) strains. The genomes of 213 AZM(r) and 23 AZM-susceptible N. gonorrhoeae isolates collected in Canada from 1989 to 2014 were sequenced. Core single nucleotide polymorphism (SNP) phylogenomic analysis resolved 246 isolates into 13 lineages. High-level AZM(r) (MICs ≥ 256 μg/ml) was found in 5 phylogenetically diverse isolates, all of which possessed the A2059G mutation (Escherichia coli numbering) in all four 23S rRNA alleles. One isolate with high-level AZM(r) collected in 2009 concurrently had decreased susceptibility to ceftriaxone (MIC = 0.125 μg/ml). An increase in the number of 23S rRNA alleles with the C2611T mutations (E. coli numbering) conferred low to moderate levels of AZM(r) (MICs = 2 to 4 and 8 to 32 μg/ml, respectively). Low-level AZM(r) was also associated with mtrR promoter mutations, including the −35A deletion and the presence of Neisseria meningitidis-like sequences. Geographic and temporal phylogenetic clustering indicates that emergent AZM(r) strains arise independently and can then rapidly expand clonally in a region through local sexual networks.